Imitation Cheese Manufacture Using Rapid Visco-Analyzer and Its Optimization. Issue 5 (3rd May 2016) - Bi, Weiwei; Li, Xiaodong; Zhao, Yongbo; Zhao, Weili; He, Shudong; Ge, Wei; Jiang, Chen
Abstract : Imitation cheeses in a laboratory-scale (100-g) made by a rapid visco analyzer (RVA) at different stirring speeds (200, 300, 450 rpm) were investigated with a control (Stephan cooker at 1, 500 rpm) at 85 °C through functional properties, microstructure and sensory evaluation. Compared to the cheeses made by the Stephan cooker, the cheese made by RVA was significantly ( P < 0.05) more green, more yellow and noticeably less white than all other cheeses, which had a decrease in the L * values and an increase in a * and b * values. TPA values of imitation cheese made by the RVA at 450 rpm were lower than that cheese made by other speed. However, the imitation cheeses of 450 rpm was significantly ( P < 0.05) higher, which was similar with the fat leakage of imitation cheese manufactured by Stephan cooker. The melt of imitation cheese significantly ( P < 0.05) reduced by increasing the stirring speed of RVA. While significant, the melt of the 1, 500 rpm cheese was smaller than all other cheeses. Increasing the stirring speed of RVA showed a more effective fat emulsification and a uniform protein matrix. Sensory analysis showed the imitation cheese made by RVA at 450 rpm was similar to the control made by Stephan cooker. Subsequently, the stirring speed, mixing time and heating temperature were optimized at 450 rpm, 7.50 min and 86 °C by response surface methodology (RSM). Results indicated that RVA could make imitation cheeses as well as the functional properties of the control in a laboratory-scale.